Perioperative management in endoscopic endonasal skull‐base surgery: a survey of the North American Skull Base Society. Issue 5 (20th December 2017) - Roxbury, Christopher R.; Lobo, Brian C.; Kshettry, Varun R.; D'Anza, Brian; Woodard, Troy D.; Recinos, Pablo F.; Snyderman, Carl H.; Sindwani, Raj
Abstract : Background: The objective of this work was to better understand variations in perioperative management in endoscopic endonasal skull‐base surgery (EESBS) and to identify trends in management based upon the practice patterns of North American Skull Base Society (NASBS) members. Methods: A 29‐question survey evaluating perioperative EESBS management was sent to all NASBS members. Responses were analyzed with descriptive statistics. Subgroup analysis was performed based on participant demographics. A Bonferroni correction was performed and a p value <0.01 was considered statistically significant for subgroup analysis. Results: Of 651 invitees, 116 responded (17.8%). Participants were primarily from the United States (81.0%), and practiced in academic centers (83.6%). The majority were neurosurgeons (55.2%) or rhinologists (27.6%). Most surgeons (83.6%) advocated use of preoperative intravenous antibiotics (96.6%) and image guidance in all cases (83.6%). Lumbar drains were not recommended for cases in which an intraoperative cerebrospinal fluid (CSF) leak was not anticipated (94.8%). Nasoseptal flaps (NSFs) were not recommended in cases without intraoperative CSF leak (84.5%), but were recommended in cases of high‐flow intraoperative CSF leak (97.4%). While postoperative restrictions were highly variable, most providers recommended CSF leak precautions (89.7%), flying restrictions (94.0%), and driving restrictions (95.6%) regardless of intraoperative CSF leak status. Most experts also recommended that continuous positive airway pressure (CPAP) be avoided for at least 2 weeks when an intraoperative CSF leak is encountered (81.9%). Conclusion: Despite variation in perioperative management of EESBS patients, important trends were identified by this study. Further investigation is needed to standardize perioperative practice patterns in EESBS.